Quark and diquark fragmentation into neutral strange particles as observed in muon-proton interactions at 280 GeV - Arneodo, M; Arvidson, A; Aubert, J; Beaufays, J; Becks, K; Bee, C; Benchouk, C; Bird, I; Blum, D; Böhm, E; de Bouard, X; Brasse, F; et al. (1984)
The production of K0s, Λs and Λs has been studied in a 280 GeV muon-proton scattering experiment with almost complete coverage of all kinematic regions. A study is made of the dependence of the multiplicities on the hadronic centre of mass energy, W, and of the Feynman x distributions. It is found that K0 and Λ production is mostly central and increases strongly with W, whereas Λ production comes mainly from the remnant target system and is only weakly W dependent. © 1984.